2000
DOI: 10.1007/s002770000219
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage in children with immune thrombocytopenic purpura

Abstract: We sent questionnaires to hospitals in Japan in order to study the incidence and conditions of intracranial hemorrhage (ICH) in children with immune thrombocytopenic purpura (ITP). From 1980 to 1995, 11 cases of ICH were reported in eight patients with ITP at 35 institutions. One patient had ICH four times, but only one patient died of the condition. From 1990 through 1995, ICH occurred in four (0.52%) of 772 patients with ITP. None of the patients died. The platelet count when ICH occurred was 5.2 +/- 3.7 x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1
15

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 3 publications
2
46
1
15
Order By: Relevance
“…Potential risk factors include platelet counts below 10 to 20 ϫ 10 9 /L, nonsteroidal anti-inflammatory drugs (NSAIDs), head trauma, vasculitis associated with systemic lupus erythematosis (SLE), and cerebral arteriovenous malformations (AVMs). 1,3,[7][8][9] This study aimed to define the features associated with ICH in ITP. Information was obtained on 40 children with ICH and 80 children with ITP as matched controls by yearly mail survey and follow-up phone calls to pediatric hematologist-oncologists across the United States from January 1987 to December 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Potential risk factors include platelet counts below 10 to 20 ϫ 10 9 /L, nonsteroidal anti-inflammatory drugs (NSAIDs), head trauma, vasculitis associated with systemic lupus erythematosis (SLE), and cerebral arteriovenous malformations (AVMs). 1,3,[7][8][9] This study aimed to define the features associated with ICH in ITP. Information was obtained on 40 children with ICH and 80 children with ITP as matched controls by yearly mail survey and follow-up phone calls to pediatric hematologist-oncologists across the United States from January 1987 to December 2000.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] However, it is widely accepted that the decision to treat thrombocytopenia should not entirely be based on the PC, but rather made in the context of clinical symptoms and disease progression. 16,18 Indeed, studies in humans have shown that the bleeding risk at reduced PCs is influenced by the individual's age, 19,20 the occurrence of trauma, 21 genetic susceptibility, environmental effects, medication, or comorbidity. [22][23][24][25] Similarly, studies in mice have shown that low PCs alone do not cause spontaneous bleeding, but rather a combination of a low platelet count and additional factors, such as binding of antibodies to endothelial cells, 26 inflammation, 27 or the nature of the target antigen of antiplatelet antibodies 28 determine the occurrence of hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…The patients who presented with ICH as the first manifestation of the ITP were excluded from treatment/cost analysis. As in previous studies, 2,5,6 head trauma and hemorrhagic manifestations (beyond mild cutaneous) were significant risk factors for ICH and, in the case of more bleeding manifestations, increased mortality. In contrast to other studies, the authors found no relationship between concurrent nonsteroidal anti-inflammatory drug use, wet purpura, and gastrointestinal or vaginal bleeding, but this may be due in part to the limitations of retrospective reporting in a survey study.…”
mentioning
confidence: 53%
“…[3][4][5] To achieve clinical efficacy in case of disseminated PTLD, it has been proposed to deliver EBV-CTLs at completion of rituximab/chemotherapy treatment, while patients are temporarily off immunosuppression. 6 As …”
Section: Patrizia Comoli Fondazione Irccs Policlinico San Matteomentioning
confidence: 99%